Anmeldelser - Jacoby, Jan (Danish Yearbook of Musicology, 1979)
Review of: Svend Westergaard: Concerto per violoncello ed orchestra, op. 26. Erling Bløndal Bengtsson, cello; Danmarks Radios Symfoniorkester; dirigent: Ole Schmidt. Pezzo concertante, op. 27. Danmarks Radios Symfoniorkester; dirigent: Francesco Cristofoli. Dansk Musikantologi 019.